Faces of literature instruction - Abdullah, Tina; Zainal, Zaidah (2008)
Literature has time and again been integrated across different curricula ranging from as early as in literacy programmes for preschool children to more advanced specialised courses offered for graduates at tertiary level. Its reputation as a cultured and prestigious subject matter has often been unreservedly understood or questioned. Through growing empirical discovery however, a more thorough understanding of its practices as well as the actual challenges in its implementation has evidently been discovered and used to support efforts in exploring, advancing and reshaping its role within different curricula. To complement empirical efforts, an understanding of the fundamental factors that have influenced the shaping of literature instruction is indispensable. Among the various factors that have contributed to the way literature has been explicated and taught are the outcome of the developments in the modern literary theories, the marriage between literature and language instruction and the influence of the evolution in educational theories and practices. Therefore, an overview of these factors and their contributions towards the shaping of faces in the literature instruction will be addressed in this paper. The awareness of these factors and how they have influenced the way literature has been taught and explicated may not only be used to understand and analyse evidence found through empirical investigation but could also be used to make vital decisions about the general pedagogical needs and practises of the literature instruction in the future.